BAHASA ISYARAT INDONESIA DALAM PROSES INTERAKSI SOSIAL TULI DAN “MASYARAKAT DENGAR” DI KOTA DENPASAR - Yohans, Jordy Alexi; Suka Arjawa, I Gusti Putu Bagus; Punia, I Nengah (JURNAL ILMIAH SOSIOLOGI: SOROT; Vol 1 No 2 (2019), 2019)
ABSTRACT   One sign language that can be used by Deaf and "hearing society" in Denpasar City is Indonesian Sign Language or abbreviated as Bisindo. The purpose of this study is to determine the implementation of Bisindo and the meaning of Bisindo in the process of Deaf social interaction and the "hearing society". This research uses descriptive type and qualitative methods also Blumer symbolic interactionism as a theory to analyze the information obtained. Implementation of the use of Bisindo in the process of social interaction needs to notice  to the existing guidelines in the language, namely variations in sign language, parameters in producing signs, and applicable grammar. There are three meanings of Bisindo for Deaf, namely as natural sign language, the fulfillment of the purpose of communication, and as an identity also as Deaf culture. Meanwhile, the meaning of Bisindo for "hearing society" is a means to communicate with the Deaf.   Keywords: Bisindo , the Deaf, meaning, symbolic interactionism